Nucleophilic Reactivities and Lewis Basicities of 2‐Imidazolines and Related N‐Heterocyclic Compounds. Issue 16 (9th April 2013) - Maji, Biplab; Baidya, Mahiuddin; Ammer, Johannes; Kobayashi, Shinjiro; Mayer, Peter; Ofial, Armin R.; Mayr, Herbert
Abstract: The nucleophilicity parameters N and s N, as defined by the linear free‐energy equation log  k (20 °C) = s N ( N  + E ), of the 2‐imidazolines1a –d and the related N‐heterocyclic compounds2 –5 have been determined by studying the rates of their reactions with differently substituted benzhydrylium ions in dichloromethane at 20 °C by stopped‐flow or laser flash photolysis techniques. It is demonstrated that the N and s N parameters thus obtained can be used to reliably predict the rate constants for their reactions with Michael acceptors of known electrophilicity E . A comparison of the nucleophilicity parameters of the imidazoline derivatives1 with other commonly used nucleophilic organocatalysts shows that they are 10 to 10 3 times less nucleophilic than PPh3, 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene, or 4‐(dimethylamino)pyridine. The structure–reactivity relationships of these heterocycles are discussed. Abstract : Rate and equilibrium constants for the reactions of 2‐imidazolines and related N‐heterocyclic compounds with diarylcarbenium ions have been measured in CH2 Cl2 at 20 °C. These data were employed to determine their nucleophilicities and Lewis basicities, which were compared with other nucleophilic organocatalysts.